Search for supersymmetry in pp collisions at root s=8 TeV in events with a single lepton, large jet multiplicity, and multiple b jets - Chatrchyan, S. (2014)
Results are reported from a search for supersymmetry in pp collisions at a center-of-mass energy of 8 TeV, based on events with a single isolated lepton (electron or muon) and multiple jets, at least two of which are identified as b jets. The data sample corresponds to an integrated luminosity of 19.3 fb(-1) recorded by the CMS experiment at the LHC in 2012. The search is motivated by supersymmetric models that involve strong-production processes and cascade decays of new particles. The resulting final states contain multiple jets as well as missing transverse momentum from weakly interacting particles. The event yields, observed across several kinematic regions, are consistent with the expectations from standard model processes. The results are interpreted in the context of simplified supersymmetric scenarios with pair production of gluinos, where each gluino decays to a top quark-antiquark pair and the lightest neutralino. For the case of decays via virtual top squarks, gluinos with a mass smaller than 1.26 TeV are excluded for low neutralino masses. (C) 2014 The Authors. Published by Elsevier B.V.